The Involvement of Metals in Alzheimer’s Disease Through Epigenetic Mechanisms - Cai, Menghua; Zhang, Xiangjin; He, Wei; Zhang, Jianmin (Frontiers in Genetics, 2020)
Alzheimer’s disease (AD) is the most common neurodegenerative diseases in the central nervous system cause of dementia. Two factors were hypothesized to be involved in the pathogenesis of AD, namely beta-amyloid cascade and tauopathy. At present, accumulating evidences suggest that epigenetics may be the missing linkage between genes and environment factors, providing possible clues to understand the etiology of the development of AD. In this article, we focus on DNA methylation and histone modification involved in AD and the environment factor of heavy metals’ contribution to AD, especially epigenetic mechanisms. If we can integrate information together, and that may find new potential targets for treatment.